Does video e-learning improve pharmacy teams' attitudes and preparedness towards suicide prevention? - Hayley C. Gorton; Hayley J. Berry; Claire L. O'Reilly; David Gardner; Andrea L. Murphy (Elsevier, 2023)
Background: Evidence on the role of pharmacy teams in suicide prevention is growing. To support pharmacy teams, a video e-learning was produced by the Centre for Pharmacy Postgraduate Education (CPPE) involving an 'on-the-sofa' style group interview with people with personal and professional experience of suicide and suicide research. Objective: The objective was to measure any change in attitudes and preparedness for suicide prevention, following a video e-learning produced for pharmacy staff. Methods: People working in any sector of pharmacy in England and who accessed the training video were invited to complete a pre- and post- training questionnaire, between September 2019 and March 2021. Question types included demographics, experiences, attitudes as measured by the Attitudes to Suicide Prevention (ASP) scale, and preparedness. Descriptive statistics were used to summarize demographics and experience and paired t-tests were used to compare pre- and post- questionnaire responses. Results: Both questionnaires were completed by 147 people. Most worked in community pharmacy (88%) and were pharmacists (64%) or pharmacy technicians (20%). Attitudes to suicide prevention improved significantly (pre:31.20 (SD 6.04); post:28.40 (SD 6.50), p < 0.0001) after watching the video, as did self-reported preparedness. Conclusions: Pharmacy teams' self-reported attitudes and preparedness for suicide prevention improved after watching this suicide awareness video compared to baseline. Suicide awareness training tailored to pharmacy teams may be valuable, but the longitudinal impact of any suicide prevention training requires further exploration.